Temporal Change in Fur Color in Museum Specimens of Mammals: Reddish-Brown Species Get Redder with Storage Time - Andrew K. Davis; Natalie Woodall; Jake P. Moskowitz; Nikole Castleberry; Byron J. Freeman (International Journal of Zoology)
Museum collections have great value for zoological research, but despite careful preservation, over time specimens can show subtle changes in color. We examined the effect of storage time on fur color of two reddish-brown species, golden mice (Ochrotomys nuttalli) and eastern chipmunk (Tamias striatus). Using image analysis, we obtained color data (hue, saturation, and density) on 91 golden mice and 49 chipmunks from Georgia, USA. Analyses that considered body size, gender, and collection year showed significant effects of year on fur color of golden mice (hue and saturation) and of agouti color of chipmunks. Older specimens tended to be redder in color than newer specimens, consistent with a prior study of red bats (Lasiurus borealis). Hair samples showed reddening of fine body hairs, but not in thicker guard hairs. There was no temporal change in black or white stripe color in chipmunks, indicating that this temporal effect would be limited to species with reddish-brown fur. This effect may be caused by breakdown of eumelanin pigments (which make dark colors) over time, leaving a greater proportion of pheomelanin pigments (which make red colors). These results show that storage time needs to be considered in research projects where fur color is of importance.